NUTRITIONAL STATUS SCREENING OF ELEMENTARY SCHOOL-AGE CHILDREN IN LELEDE VILLAGE - Syaidatussalihah Hasan (Jurnal Pengabdian Masyarakat Sehati, 2022)
Stunting is problem of chronic malnutrition caused by a lack of nutrition for a long time, resulting in impaired growth in children, namely the child's height is lower or shorter (dwarf) than the standard age. From the results of interviews with several mothers who have school-age children in Lelede Village, it is known that there is not much exposure to stunting. So that some of them concluded that children who are shorter than their age are a genetic factor so they do not require further treatment. Therefore, the purpose of this community service activity is to invite parents to play a role in preventing stunting to improve the health status of their children. Based on existing data, an overview of nutritional status based on height/age shows that the number of children with short stature is 20%, the number of children with normal stature is 78%, while the total number of children with tall stature is only 2%. Furthermore, the description of nutritional status based on BMI/U shows that 12% of children have undernourished status, 76% of children with normal nutritional status, 8% of children with overweight nutritional status, while 4% of children with obese nutritional status.